(untitled) (KRINOK: JURNAL ARSITEKTUR DAN LINGKUNG BINA, 2022)
Nowadays, developments and requirements in architectural design leads to the sustainable design concept that are responsive to its environment. The application of sustainable design at the Al-Falah Mosque can be observed on the building’s exterior and interior expressions, where the building design principles provide impacts on ecological, social and economic. The methods used in this research is a mix method, namely the merger between qualitative and quantitative descriptive analysis. The analysis refers to field observations data of the architectural expression include exterior and interior. Research results also showed that the application of sustainable design in the building is a bioclimatic architecture concept and well-applied. One things that influential aspects of sustainable design is the façade treatment that uses passive bioclimatic architecture concepts, and the façade are arranged in the form of calligraphy through the supergraphic pattern becomes characteristic of Al-Falah Mosque.